2015
DOI: 10.1088/0268-1242/30/9/094001
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of bismuth induced changes in the band structure of dilute Ga–V–Bi and In–V–Bi alloys: chemical trends versus experimental data

Abstract: Bi-induced changes in the band structure of Ga-V-Bi and In-V-Bi alloys are calculated within the density functional theory (DFT) for alloys with Bi ⩽3.7% and the observed chemical trends are discussed in the context of the virtual crystal approximation (VCA) and the valence band anticrossing (VBAC) model. It is clearly shown that the incorporation of Bi atoms into III-V host modifies both the conduction band (CB) and the valence band (VB). The obtained shifts of bands in GaP 1−x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 52 publications
9
42
0
Order By: Relevance
“…To improve the description of the band structure of regular LDA/GGA approach, we have used the modified Becke-Johnson exchange potential with LDA correlation (MBJLDA) 29,30 for all our band structure calculations. This approach has been proven by us to be very effective and efficient numerous times over the years in more traditional III-V semiconductors 31,32 as well as in TMDs in Ref. 28 where a detailed reasoning of this choice is presented.…”
Section: A Band Structure Calculationsmentioning
confidence: 99%
“…To improve the description of the band structure of regular LDA/GGA approach, we have used the modified Becke-Johnson exchange potential with LDA correlation (MBJLDA) 29,30 for all our band structure calculations. This approach has been proven by us to be very effective and efficient numerous times over the years in more traditional III-V semiconductors 31,32 as well as in TMDs in Ref. 28 where a detailed reasoning of this choice is presented.…”
Section: A Band Structure Calculationsmentioning
confidence: 99%
“…In the calculations reported in this paper, band offset ratios of 60:40 between the strained InGaAs and GaAs and 24:76 between the strained GaAsBi and GaAs were used, respectively. 6,31 The transformation of GaAsBi and In 0.2 Ga 0.8 As to form a type-II configuration from a type-I configuration is estimated to occur near a Bi concentration of 1.3%. A schematic diagram of the conduction and valence bands in the active region of our structure is shown in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…1-3 The incorporation of a small amount of Bi atoms into GaAs strongly reduces the band-gap energy (84-91 meV/%Bi) [4][5][6] and, in addition, decreases the temperature coefficient of the band gap from 0.45 meV/K to about 0.15 meV/K. 2,7 For GaAsBi with Bi contents of above 10%, the spin-orbit splitting energy (D SO ) becomes larger than the band gap, and thus, the hot-holegenerating Auger recombination and the inter-valence band absorption processes are expected to be suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…This large band-gap bowing is mainly the result of a prominent valence band anti-crossing interaction between resonant Bi energy levels and the GaAs host matrix, which results in a non-linear upward shift of the valence band edge 15 . Whilst the proximity of the Bi induced energy levels close to the valence band edge strongly affects its electronic structure, it has also been shown that the incorporation of Bi also modifies the conduction band 16 , with a linear downward shift of 33 meV/%Bi observed in GaAsBi quantum wells containing up to 5.9% Bi 17 .…”
Section: Introductionmentioning
confidence: 99%